The Founders on Religion : A Book of Quotations - Hutson, James H. (Book collections on Project MUSE., 2005)
What did the founders of America think about religion? Until now, there has been no reliable and impartial compendium of the founders' own remarks on religious matters that clearly answers the question. This book fills that gap. A lively collection of quotations on everything from the relationship between church and state to the status of women, it is the most comprehensive and trustworthy resource available on this timely topic. The book calls to the witness stand all the usual suspects--George Washington, Thomas Jefferson, James Madison, Benjamin Franklin, and John Adams--as well as many less.